Heartwood Proportion and Physical-Mechanical Properties of Three Diameter Class of Gelam Wood (Melaleuca sp) from Central Kalimantan - Wahyu Supriyati; Tibertius A Prayitno; Soemardi Soemardi; Sri M Marsoem (Masyarakat Peneliti Kayu Indonesia, 2014)
Gelam wood commonly use for house pole in peatswamp land of Central Kalimantan. However increasing the utilization of gelam wood lead to harvest a small diameter of trees. This research aims to study the percentage of heartwood, physical mechanical properties of gelam wood of different diameter class.Keyword: diameter class, gelam wood, heart wood, physical mechanical properties